A Modern Treatment of the Ricardian Economy: - Samuelson, Paul A. (Quarterly Journal of Economics, 1959)
Back to the beginning, 217. — Time and interest, 219. — Failure of the labor theory, 220. — A simple corn economy, 222. — The special timeless case, 222. — The extreme Torrens-Ricardo Case, 223. — Land scarcity and falling interest, 225. — A long-run, constant floor for interest, 227. — The land theory restated, 228. — A final word, 230.